The Parental Blueprint: Early Childhood Lifestyle Habits and Family Factors Predict Opting for Middle Childhood Sport Involvement - Stéfanie Routhier-Guilmette; Kianoush Harandian; Sophie-Anne Turcotte; Nairy Kazandjian; Matteo Privitera; Linda S. Pagani (Children, 2025)
Background/objectives: Early childhood is marked by rapid physical and cognitive development, underscoring the critical influence of parental choices in shaping habits, pastimes, and traditions. The World Health Organization highlights habits of physical activity, sleep, and screen use as modulators of healthy development and well-being in young children. As a first, this birth cohort study investigates the relationship between movement behaviors in toddlerhood and subsequent sport participation during middle childhood. Methods: Participants are 930 boys and 926 girls from the Quebec Longitudinal Study of Child Development. Using a population-based analytical approach, we examined the relationship between parent-reported active leisure, sleep, and sedentary screen time at age 2 years and trajectory of sport participation between ages 6 and 10 years using sex-stratified linear regressions that account for a range of pre-existing individual and family confounding factors. Results: Many child and family characteristics predicted early childhood movement behaviors, distinctly for boys and girls. Moreover, parental regulation of screen time during early childhood significantly influenced their decisions to enroll and encourage sport participation in sons during school age. Specifically, boys who spent more than 1 h/day on screens had 10% fewer chances of consistently participating in sport throughout middle childhood, even after accounting for adherence to other lifestyle habits. Conclusions: Our findings suggest that parental values regarding early childhood screen exposure are an effective potential target for intervention fostering healthy and active development. Future research should focus on parent and child motivations for sport involvement in the long-term.